2021
DOI: 10.3389/fneur.2021.743135
|View full text |Cite
|
Sign up to set email alerts
|

Altered Degree Centrality of Brain Networks in Parkinson's Disease With Freezing of Gait: A Resting-State Functional MRI Study

Abstract: Freezing of gait (FOG) in Parkinson's disease (PD) leads to devastating consequences; however, little is known about its functional brain network. We explored the differences in degree centrality (DC) of functional networks among PD with FOG (PD FOG+), PD without FOG (PD FOG–), and healthy control (HC) groups. In all, 24 PD FOG+, 37 PD FOG–, and 22 HCs were recruited and their resting-state functional magnetic imaging images were acquired. The whole brain network was analyzed using graph theory analysis. DC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Compared with HCs, decreased BC has been found in several brain regions, mainly located in the prefrontal cortex, supplementary motor area, hippocampus, cingulate gyrus, and occipital gyrus bilateral striatum, and increased centrality in the right olfactory cortex in PD FOG+ patients. Abnormalities in these brain regions have been reported by previous studies (Mitchell et al, 2019;Brugger et al, 2020;Ruan et al, 2020;Jin et al, 2021a). The prefrontal cortex plays an important role in cognitive and executive functions (Teffer and Semendeferi, 2012).…”
Section: The Difference In Nodal Parameters Between Groupsmentioning
confidence: 70%
See 3 more Smart Citations
“…Compared with HCs, decreased BC has been found in several brain regions, mainly located in the prefrontal cortex, supplementary motor area, hippocampus, cingulate gyrus, and occipital gyrus bilateral striatum, and increased centrality in the right olfactory cortex in PD FOG+ patients. Abnormalities in these brain regions have been reported by previous studies (Mitchell et al, 2019;Brugger et al, 2020;Ruan et al, 2020;Jin et al, 2021a). The prefrontal cortex plays an important role in cognitive and executive functions (Teffer and Semendeferi, 2012).…”
Section: The Difference In Nodal Parameters Between Groupsmentioning
confidence: 70%
“…In our previous study on the functional brain network of FOG in PD, we found that PD FOG+ patients showed decreased DC in MFG, inferior temporal gyrus (ITG), STG, middle temporal gyrus (MTG), and parahippocampal gyrus (PhG) (Jin et al, 2021a). These findings suggest that PD FOG+ patients have some commonalities and differences in brain regions with impaired functional and structural brain networks.…”
Section: The Difference In Nodal Parameters Between Groupsmentioning
confidence: 83%
See 2 more Smart Citations
“…Functional magnetic resonance imaging (fMRI) is a non-invasive technique that can be used to study brain function changes in a variety of diseases, providing valuable information for explaining pathogenesis and guiding clinical practice ( Mulders et al, 2015 ; Puschmann and Thiel, 2017 ; Vos et al, 2017 ; Xia et al, 2017 ; Tang et al, 2019 ; Jin et al, 2021 ). According to previous studies, resting-state fMRI (rs-fMRI) can reflect underlying neuronal activity ( Logothetis, 2002 ; Qi et al, 2015 ; Zhu et al, 2019 ; Qian et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%